1995
DOI: 10.1007/bf01719947
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosamine, nitrate and nitrite in relation to gastric cancer: A case-control study in Marseille, France

Abstract: A case-control study on gastric cancer and diet was conducted in Marseille (France). Ninety-two patients with histologically confirmed adenocarcinoma and 128 controls undergoing functional reeducation for injuries or trauma were interviewed by a trained dietician using a dietary history questionnaire on their usual diet during the year preceding the first symptoms for cases, or preceding interview for controls. Intake of nitrite, nitrate and pre-formed N-nitrosodimethylamine (NDMA) from food was estimated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
52
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(55 citation statements)
references
References 20 publications
3
52
0
Order By: Relevance
“…In most studies a statistically significant inverse association was reported between nitrate intake from foods and gastric cancer risk (Risch et al, 1985;Buiatti et al, 1990;Boeing et al, 1991;Gonzalez et al, 1994;Hansson et al, 1994;La Vecchia et al, 1994), which disappeared after additional adjustment for potential confounders (mainly intake of vitamin C and beta-carotene). In all case-control studies on nitrate and gastric cancer risk, a positive association was reported (Risch et al, 1985;Buiatti et al, 1990;Gonzalez et al, 1994;Hansson et al, 1994;La Vecchia et al, 1994;Pobel et al, 1995) which reduced after adjustment for intake of other nutrients.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In most studies a statistically significant inverse association was reported between nitrate intake from foods and gastric cancer risk (Risch et al, 1985;Buiatti et al, 1990;Boeing et al, 1991;Gonzalez et al, 1994;Hansson et al, 1994;La Vecchia et al, 1994), which disappeared after additional adjustment for potential confounders (mainly intake of vitamin C and beta-carotene). In all case-control studies on nitrate and gastric cancer risk, a positive association was reported (Risch et al, 1985;Buiatti et al, 1990;Gonzalez et al, 1994;Hansson et al, 1994;La Vecchia et al, 1994;Pobel et al, 1995) which reduced after adjustment for intake of other nutrients.…”
Section: Discussionmentioning
confidence: 96%
“…Case-control studies have mainly investigated the association between nitrate or nitrite from foods and gastric cancer risk (Risch et al, 1985;Buiatti et al, 1990;Boeing et al, 1991;Palli et al, 1992;Gonzalez et al, 1994;Hansson et al, 1994;La Vecchia et al, 1994;Pobel et al, 1995). In most studies a statistically significant inverse association was reported between nitrate intake from foods and gastric cancer risk (Risch et al, 1985;Buiatti et al, 1990;Boeing et al, 1991;Gonzalez et al, 1994;Hansson et al, 1994;La Vecchia et al, 1994), which disappeared after additional adjustment for potential confounders (mainly intake of vitamin C and beta-carotene).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, that conclusion was based mainly on casecontrol studies, which are more susceptible to systematic bias than prospective cohort studies, and recent prospective studies have been inconsistent. [3][4][5][6] Besides much salt and nitrites or nitrates, processed meat products like bacon, sausage and ham often contains carcinogenic nitrosamines.7-9 N-nitrosodimethylamine (NDMA) is the most frequently occurring nitrosamine in foods.10 Nitrosamines can also be formed endogenously in the stomach through nitrosation of nitrite with amines.7 To date, 5 case-control studies [11][12][13][14][15] and only 1 prospective cohort study 3 with a small number of cases (n 5 68) have investigated the association between NDMA or nitrosamine intake and stomach cancer risk, with 4 case-control studies [11][12][13]15 showing a positive association.To examine whether associations exist between intake of processed meat and NDMA and risk of stomach cancer, we used prospective data from the Swedish Mammography Cohort, a large population-based cohort with 18 years of follow-up and repeated assessments of diet. In addition, we evaluated risk of stomach cancer in relation to consumption of red meat, poultry and fish.…”
mentioning
confidence: 99%
“…10 Nitrosamines can also be formed endogenously in the stomach through nitrosation of nitrite with amines. 7 To date, 5 case-control studies [11][12][13][14][15] and only 1 prospective cohort study 3 with a small number of cases (n 5 68) have investigated the association between NDMA or nitrosamine intake and stomach cancer risk, with 4 case-control studies [11][12][13]15 showing a positive association.…”
mentioning
confidence: 99%